Reorganizing the agricultural bureaucracy for the 21st century trends, issues, and policy questions - De Vera, J. Prospero E., III (1997)
In order to improve the efficiency of the various line departments concerned with the agricultural sector as a whole, we should look closely at their respective purposes and responsibilities, which more often than not result in the duplication and overlapping of functions. The overall effect of the fragmentation and multiplicity of delivery systems is the problem of locating accountability for agricultural development, duplication of programs and wastage of public funds. Since effective pressure cannot be put to improve performance, agriculture agencies continue to receive annual appropriations with very little incentive to work on integration and rationalization.
Keywords: Accountability for Agricultural Development; Agricultural subsidies; Bureau of Agriculture; Bureaucratization; Agricultural productivity; Cooperative Development Authority; Philippines. Department of Agriculture; Philippines. Department of Environment and Natural Resources